(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces new classes of multifunctions between bitopological spaces, namely upper almost contra-(τ_1,τ_2)-continuous multifunctions and lower almost contra-(τ_1,τ_2)-continuous multifunctions. Furthermore, several characterizations of upper almost contra-(τ_1,τ_2)-continuous multifunctions and lower almost contra-(τ_1,τ_2)-continuous multifunctions are considered.